Effects of trace calcium and strontium on microstructure and properties of Cu-Cr alloys. (10th June 2022) - Ma, Muzhi; Xiao, Zhu; Meng, Xiangpeng; Li, Zhou; Gong, Shen; Dai, Jie; Jiang, Hongyun; Jiang, Yanbin; Lei, Qian; Wei, Haigen
Highlights: The additions of Ca and Sr improve the softening resistance of the Cu-Cr alloy. The Cu-Cr-Ca and Cu-Cr-Sr alloys have smaller Cr precipitates with FCC structure. The Cu-Cr-Ca and Cu-Cr-Sr alloys recrystallize more difficultly. Dislocations and precipitates make main contribution to high strengths of alloys. Ca and Sr atoms tend to segregate at interface between precipitates and matrix. Abstract: Cu-0.57Cr-0.01Ca and Cu-0.58Cr-0.01Sr (wt.%) alloys were fabricated and processed by thermo-mechanical treatment. Their mechanical and electrical properties and microstructure were investigated in detail and compared with those of a Cu-0.57Cr (wt.%) alloy. The results showed that the softening resistance of the Cu-Cr alloy was significantly improved by the additions of Ca and Sr elements. Compared with the Cu-Cr alloy, the deformation microstructure of the Cu-Cr-Ca and Cu-Cr-Sr alloys was more difficult to recrystallize at elevated temperatures, and the Cr precipitates in the Cu-Cr-Ca and Cu-Cr-Sr alloys were smaller in size and had an FCC structure at any given aging state. The high strengths of the Cu-Cr-Ca and Cu-Cr-Sr alloys were mainly attributed to the dislocation strengthening provided by high-density dislocations and the precipitate strengthening provided by fine Cr precipitates. First-principles calculation showed that the segregations of Ca and Sr atoms at interface between Cr precipitates and copper matrix were favorable in energetics. This segregation effectively hindered the growth of Cr precipitates and significantly enhanced the pinning effect on the motion of dislocations and subgrain boundaries, eventually leading to the improvement in the softening resistance of the Cu-Cr alloy.